Emprego e renda no Maranhão: uma interpretação sobre as transformações socioeconômicas observadas entre 2012 e 2022 - FERREIRA, Lucas de Queiroz (2025)
Considering the importance of employment and its direct influence on the social health of a country, understanding work patterns is fundamental, as it facilitates individuals' access to rights and development opportunities. Thus, this study analyzed the main socioeconomic transformations in the Maranhão labor market between 2012 and 2022, adopting a quantitative- descriptive approach. The research explored the dynamics of employment in the state, based on theoretical references about the labor market and its structural transformations. Secondary data from the Continuous National Household Sample Survey (PNADc), carried out quarterly by IBGE, were used, complemented by a bibliographical review. The variables analyzed included indicators such as unemployment rate, combined unemployment rate and potential workforce, in addition to the discouragement rate, labor force participation, informality, workforce composition, female participation and gender wage differences. The results indicated that the unemployment rate did not adequately reflect the local reality, since many workers migrated to inactivity instead of remaining unemployed, which was evidenced by the increase in the discouragement rate. Another relevant finding was the relative improvement in female income, only in scenarios of a drop in the average salary in the private sector. Furthermore, a reduction in informality was observed, although levels remained high. Factors such as lack of investment, economic crises, labor reform, local history and regional structural challenges, such as deficiencies in infrastructure and education, were significant obstacles to the sustainable development of the labor market.